THE CONCEPT OF MULTICULTURAL ISLAMIC EDUCATIONAL VALUES IN HIGHER EDUCATION (Phenomenology study on MKDU at STKIP PGRI Sidoarjo) - Abd Syakur; Abdul Muid; Lutfi Hakim; M. Khusni Mubarok (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2022)
The process of instilling the values of multicultural Islamic education basically emphasizes the principles of mutual understanding, respect, respect, fairness, tolerance, and equality to create harmony and keep away from intolerant practices between religious communities. The principle of value in the view of Islam does not regard differences in religion, race, ethnicity, and culture as issues that must be opposed. This study aims to determine the results of the concepts and principles and the process of instilling the values of multicultural Islamic education through the basic course material at STKIP PGRI Sidoarjo. This study used a qualitative approach with descriptive analytic data analysis. Data collection was carried out by interview, observation, and documentation techniques. Data analysis techniques include data reduction, data presentation, and drawing conclusions. Checking the validity of the findings was carried out using source and method triangulation techniques. The results of this study indicate that the concepts of instilling the values of multicultural education at STKIP PGRI Sidoarjo are based on several principles of openness, tolerance, togetherness, and unity in diversity based on an understanding of Islam that is rahmatan lil'alamin. Multicultural knowledge contains knowledge about the values of multicultural Islamic education, while multicultural feeling includes instilling a multicultural sense in students. Based on this, Islam is able to create harmony and peace, so Islamic education with a multicultural spirit needs to be provided and included in the higher education curriculum